Analisis Hotspot Cluster: Tinjauan Pola Spasial dari Ketersediaan Fasilitas Kesehatan dan Penduduk di Kalimantan Indonesia - Silalahi, Stevay David Christian; Azharuadin, Muhammad; Sihombing, Rina Dini Mariati; Khasanah, Wulan Ely; Sianipar, Reinhard Jordan (Universitas Pendidikan Ganesha, 2024)
Everyone has the right to access health facilities, including the residents of Kalimantan Island. The focus of this study is on applying spatial analysis to find trends in the distribution of health services across the island of Kalimantan. In order to ascertain the clustering of locations with high (hotspot) and low (coldspot) concentration of health facilities, this study used the Getis-Ord Gi* hotspot analysis and the Moran's I spatial autocorrelation test. Population concentartion was also examined for additional analysis. The findings indicate that there are five coldspots in places like Sambas and Kapuas Hulu Regencies, in addition to two hotspots in Pontianak City and Balikpapan City. According to other findings, there is a significant positive link between the number of health facilities and high population density locations, such as urban areas, whereas distant and border areas typically have less health services in terms of spatial arrangement. The government can use the recommendations from this study to plan a more fair and efficient distribution of health services in Kalimantan.